Synthesis, structural characterization and dielectric behavior of new oxime-cyclotriphosphazene derivatives - Koran, Kenan; Özen, Furkan; Biryan, Fatih; Görgülü, Ahmet Orhan (My University, 2016)
The cyclotriphosphazene compound (2) bearing formyl groups as side groups was obtained from the reaction of 2,2-Dichloro-4,4,6,6-bis[spiro(2?,2?-dioxy-1?,1?-biphenylyl)]cyclotriphosphazene (1) with 4-hydroxy-3-methoxybenzaldehyde in the presence K2CO3 in tetrahydrofuran. Oxime-cyclotriphosphazene compound (3) was synthesized from the reaction of compound 2 with hydroxylamine hydrochloride in pyridine. The synthesized oxime-phosphazene compound (3) was reacted with alkyl and acyl halides. As a results, the cyclotriphosphazene compounds (1–10) bearing oxime ether and ester as side groups were obtained. The chemical structures of these compounds (1–10) were determined by elemental analysis, FT-IR, 1H, 13C and 31P NMR spectroscopic methods. Dielectric constant, dielectric loss factors and conductivity properties of cyclotriphosphazene compounds were measured over the frequency range from 100 Hz to 2 kHz at 25 °C and compared with each other. It is found that ester substituted cyclotriphosphazenes have higher dielectric constant. Our study suggests that these phosphazenes promising candidate materials in multifunctional optoelectronic devices.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Makale - Yabancı Dilde Makale
Keywords: Cyclotriphosphazene; Oxime ether and ester; Oxime-phosphazenes; Dielectric constant; Conductivity